Perceived Needs of Youth Experiencing Homelessness and Precarious Housing: Youth and Service Provider Perspectives - D'Amico, Laura (Université Saint-Paul / Saint Paul University, 2021)
Youth experiencing homelessness face a variety of significant challenges and rely on services to address many of their needs. When seeking to address these needs, there are two key sets of voices to consider: the voices of service providers, and the voices of the youth themselves. The present study aims to explore the needs of youth experiencing homelessness from these two perspectives, as well as to investigate whether any significant differences exist between the priorities of the two groups. Focus groups with youth experiencing homelessness and interviews with service providers were conducted in order to explore the challenges and needs of youth experiencing homelessness, and the qualitative data obtained was subjected to thematic analysis. The results showed several similarities, as well as several differences between the understandings of the two parties of the needs of youth experiencing homelessness. Overall, youth participants primarily discussed topics related to improving their quality of life while homeless, while service provider participants additionally focused on topics related to youth getting out of homelessness. Both groups of participants identified significant challenges with the accessibility of existing services, and emphasized the need for more services for youth specifically. The results suggest that some gaps do exist between what youth and service providers identify as the needs of youth experiencing homelessness, but that service providers value the voices of the people they serve. Another significant interpretation of the results is that neither service providers nor youth experiencing homelessness are fully satisfied with the support that is currently available, and that changes should be made.
Keywords: Youth homelessness; Homelessness; Homeless youth; Needs of homeless youth; Homeless youth needs; Precarious housing; Canada homelessness; Youth homelessness Canada; Youth experiencing homelessness; Homeless youth perspectives